Calidad de servicios en la Facultad de Ciencias Administrativas de la Universidad Técnica de Cotopaxi - Caseres Llumiguano, Digna Narcisa (2019)
The present research was carried out Administratives Sciences Faculty at Technical University of Cotopaxi, Matriz Campus, located in Av. Simon Rodriguez, Canton Latacunga, Cotopaxi Province. The goal was to evaluate the level of service quality which is provided for the faculty mentioned before. The methodology applied was quantitative type, descriptive level, non-experimental cross-sectional design. The SERVQUAL instrument proposed by Parasuraman, Zeithaml and Berry (1985) was used in order to get data collection. It consists of five dimensions (reliability, response capacity, security, empathy and tangible elements), 22 questions; expectations and perceptions items respectively. The population’s study was 141 users among the teaching staff and students at Administratives Sciences Faculty. The results obtained showed that the service quality according to people surveyed perception has a low level into the features: reliability, responsiveness and empathy. It refers to the ability to provide the promised service, the employees’ willingness in order to help the customers and the individualized attention offered by employees; except for the tangible elements and security dimensions since a positive result was demonstrated; that relates to the knowledge and attention shown by workers and the appearance of physical facilities, equipment, employees and communication material. Regarding expectations, it can be seen that customers expect to get the best service from employees and the faculty demonstrating a positive result in terms of five dimensions. It is concluded that the expectations expected by the users are greater than those received. It is generally important that the Administratives Sciences Faculty continuously makes frequent reviews on clients’ perception about the service provided. SERVQUAL is an excellent tool to carry it out, so that control and monitoring of the service will be carried out. These actions will avoid problems, complaints, discomforts of the customers and improve the services provided